2008
DOI: 10.1108/02635570810868362
|View full text |Cite
|
Sign up to set email alerts
|

Competitive intelligence process and tools for intelligence analysis

Abstract: PurposeThe purpose of this survey research is twofold. First, to study and report the process that is commonly used to create and maintain a competitive intelligence (CI) program in organizations. And second, to provide an analysis of several emergent text mining, web mining and visualization‐based CI tools, which are specific to collection and analysis of intelligence.Design/methodology/approachA range of recently published research literature on CI processes, applications, tools and technologies to collect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
59

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(231 citation statements)
references
References 15 publications
(30 reference statements)
1
146
0
59
Order By: Relevance
“…This is also referred in case of competitive intelligence which drives mission of the organization and vice versa. Because competitive intelligence focus, analysis, and communication is dependent on mission and vice versa (Bose, 2008;Calof & Wright, 2008;Nasri, 2012;Tanascovici, & Hagiu, 2013;Sun & Wang, 2015).…”
Section: Strategic Planning/strategy Formulation: I) Developing or Upmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also referred in case of competitive intelligence which drives mission of the organization and vice versa. Because competitive intelligence focus, analysis, and communication is dependent on mission and vice versa (Bose, 2008;Calof & Wright, 2008;Nasri, 2012;Tanascovici, & Hagiu, 2013;Sun & Wang, 2015).…”
Section: Strategic Planning/strategy Formulation: I) Developing or Upmentioning
confidence: 99%
“…Comprehensively called competitive intelligence is an ethical and systematic process, program and function of gathering, analyzing, and managing information about the external environment (Nasri & Zarai, 2013). This information can be used for making decisions at any level, leading to competitive advantage (Weiss, 2002;Bose, 2008;Nasri, 2012;Nasri & Zarai, 2013). External environment is composed of opportunities and threats (David, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A análise é a etapa reconhecida como a que mais agrega valor ao ciclo de IC, pois abriga o processo de transformação de dados e informações em IC (HERRING, 1988;CORY, 1996;JIN e BOUTHILLIER, 2006;BOSE, 2008).…”
Section: Competitive Intelligence As Business Process Innovationunclassified
“…Previous studies of the BI processes of large companies (Bose, 2008;Calof and Wright, 2008;Halonen and Hannula, 2007;Koskinen et al, 2005;Pirttimäki and Hannula, 2002) have revealed that larges companies have organised the use of BI in a systematic way and that they are ready to invest more to develop their BI processes. Still, BI is usually integrated into parts of other business activities.…”
Section: Conceptual Backgrounds Of Business Intelligence and Relevantmentioning
confidence: 99%
“…BI offers one means to accomplish this (Bose, 2008) The purpose of this paper is to draw a general picture of the conditions of BI and the role of external information in the SMEs of the Finnish shipbuilding industry, to identify the most essential needs and challenges and to propose actions to support individual firms and the development of that sector. The specific focus on SMEs is not only policy relevant (Small Business Act of the Commission of the European Communities, 2008), but typifies the structure of the industry, since over 80% of firms in the shipbuilding industry in the EU-27 countries are SMEs (ECORYS, 2009).…”
Section: Introductionmentioning
confidence: 99%